The Analysis of Sustainability Report As a Form of Corporate Social Responsibility Implementation Based on Global Reporting Initiative (GRI) Guidelines (Case Study at PT. Telekomunikasi Indonesia, Tbk) - Hajir Prisna Sugeng Putri; Didied Poernawan Affandy (Jurnal Ilmiah Mahasiswa FEB, 2013)
The main purpose of this research is to gain information and understanding about the level measurement of PT Telekomunikasi Indonesia sustainability report fulfillment based on performance indicators in Global Reporting Initiative (GRI) guidelines. The performance indicators that will be analyzed include economic, environment, labor practices and decent work, human rights, society and product responsibility.  The researcher compared the performance indicators in the sustainability report with Global Reporting Initiative (GRI) standard and then analyzes the standard fulfillment for  those performance indicators. Standard fulfillment has three criteria that include standard fully fulfilled, standard partially fulfilled and standard not fulfilled.   The result of this research is the 2012 sustainability report of PT Telekomunikasi Indonesia has already reported performance indicators that recommended by Global Reporting Initiative (GRI). PT Telekomunikasi Indonesia sustainability report has fully fulfilled 45 indicators out of 84 indicators that covers in each performance indicators and this sustainability report has externally assured by Mazars. Based on the comparison between analysis result and GRI application level, the 2012 sustainability report of PT Telekomunikasi Indonesia can be graded with B+. Keyword: Sustainability Report, GRI, PT Telekomunikasi Indonesia